Kebudayaan Sebagai Pembimbing Kebijakan Publik (Upacara Adat Perkawinan Suku Kutai di Tenggarong, Kalimantan Timur) - Florentinus Sudiran Ayu Apriana, Dwi Ady Saputra dan Muhammad Renaldi (Prodi Ilmu Administrasi Negara, 2018)
The aim of this research is to know the tradition of the Kutai etnic group’smarriage. The location of the research is in East Kalimantan Province fromSepember to December 2017. The sample is in Tenggarong Regency. Themethod of it is qualitative one. The results of the it is as follows : (1) TheKutai etnic group lives along the river area of Mahakam, (2) They areactually are Dayak etnic group but fetr they follow the Islam religion andthen they are called Halok or halo etnic group to differenciate from Dayaketnic group, (3) They are origionally from Tunjung etnic group, one of theDayak concerned, (4) They are Melay type whom they came here 3.000 yearsgo, (5) They have the tradition of mariage ceremony consists of (5.1) TheBepacar is to redden the nail of the fingers of the couple candidates, (5.2)Mendi-mendi is to water the couple candidates by flowered water, (5.3)Bealis is couple candidates to give eyes list, (5.4) Naik pengantin is to makemale marriage candidates to join in the folkgroup ceremony walking fromhis home to his candidate parents in law where the female candidatemarriage stays, (5.5) Geta ceremony is to make the couple candidaates to sitside by side,here the keypersns read the Islamic ceremony called tarsul inthe form of Arabic poems, (5.6) Naik Mentua is to go to the parents of themale candidate here the couples are watred the feet on the plate, to cut thepeak of coconut leaf. The suggestions of the reasearcher is that thisceremony has to be maintained as the asset of the Indonesian nation because(1) In those proceses have many advice to the youngters to apprciate theparents and the other soft skills advice, (2) This ceremony is the identity ofthe etnicgroup of Kutai, (3) To be the tools of the tourism promotion to getthe original regional income to develop the region, (4) The government ofEast Kalimantan Province should indeed utilize this process of the mariagecorrelated to the public policy in some cases